2004
DOI: 10.1628/0015221042396113
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Equity Aspects of Alternative Social Security Rules

Abstract: This paper studies human-capital formation, labor-supply, and retirement decisions associated with four alternative regimes of social security. We implement a theoretical model with overlapping generations of households and two different ability types within each generation. We find that with a given social security contribution rate, it is better to transfer income to the elderly as old-age benefits, paid independently of labor-market status. This holds with both Bismarckian and Beveridgean benefits. With suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…In consequence, schooling effort rises further, a result already found by Jensen et al . (2004) in a numerical study and confirmed by Montizaan et al . (2010) in a quantitative study.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…In consequence, schooling effort rises further, a result already found by Jensen et al . (2004) in a numerical study and confirmed by Montizaan et al . (2010) in a quantitative study.…”
Section: Introductionsupporting
confidence: 70%
“…Furthermore, actuarially adjusted arrangements like old-age benefits lead to later retirement compared to a retirement subsidy scheme and therefore prolong the period of yield for human capital investment. In consequence, schooling effort rises further, a result already found by Jensen et al (2004) in a numerical study and confirmed by Montizaan et al (2010) in a quantitative study. Finally, Cascarico and Devillanova (2008) explore the consequences of funding social security in a model of human capital investment and capital skill complementarity in production.…”
Section: Introductionsupporting
confidence: 58%
“…We count those as receiving social security pensions whose household received a payment for at least one year of the entire period length. Retirement schemes can be classified into Bismarckian systems, where earnings-related pensions are mainly financed by earnings-related contributions, and Beveridgean systems, characterized by tax-financed, flat-rate benefits providing an old-age income adequate enough to ensure a basic living standard (Jensen et al;2004). Germany, South Korea, Switzerland, and the US follow the Bismarckian tradition, while the UK, and Australia follow the Beveridgean tradition.…”
Section: Redistribution In the Long Runmentioning
confidence: 99%
“…To evaluate the resulting pattern, we make use of the welfare state classification presented in Table 1 in the Introduction, now applied to the public pension system only. Accordingly, retirement schemes can be classified into Bismarckian systems, where earnings-related pensions are mainly financed by earnings-related contributions, and Beveridgean systems, characterized by tax-financed, flat-rate benefits providing an old-age income adequate to ensure a minimum standard of living (Jensen et al;2004). Germany, South Korea, Switzerland, and the United States follow the Bismarckian tradition, whereas Australia and the United Kingdom are known for their Beveridgean pension systems.…”
Section: Redistribution In the Long Runmentioning
confidence: 99%
“…As mentioned, Australia does not provide information on public pensions in the CNEF data, meaning that we must exclude it from this exercise as well. On the one hand, we expect that Beveridgean systems are more redistributive from an intergenerational perspective (i.e., between pensioners and non-pensioners), given that pension schemes are less earnings-dependent in these welfare states and, thus, more equalizing (Jensen et al;2004). On the other hand, Bismarckian systems, which we would expect to be less intergenerationally redistributive given their more pronounced dependence on individual earnings, often provide generous means-tested minimum pensions and top-cap pensions for high-income earners, so they might eventually turn out to be highly intergenerationally redistributive as well.…”
Section: Redistribution In the Long Runmentioning
confidence: 99%